A retrospective study to compare episodic and prophylactic factor viii treatment in severe haemophilia A patients at Pietersburg Hospital - Tshipeng, Jean Paul Mulang (My University, 2023)
Introduction. The purpose of this study was to describe and compare episodic and prophylactic treatment regimens with factor VIII in paediatric patients living with severe haemophilia A at Pietersburg Hospital in Limpopo province, South Africa. Study design. Anonymised patient record data was collected retrospectively from the haemophilia treatment centre in Pietersburg Hospital, the site responsible for treating paediatric patients living with severe haemophilia A in the province. Objectives. Annualised bleeding rates and factor VIII consumption were analysed and compared between the two groups. Results. The results of the study showed that compared to the episodic group, participants in the prophylactic group had a substantial reduction in annualised bleeding rates per patient with a median of 4 vs 6 but a higher consumption of factor VIII. The annual median factor VIII consumption was 12000 IU vs 4000 IU per patient for prophylactic and episodic group respectively. Conclusion. These findings suggest that treatment of paediatric patients living with severe haemophilia A using low-dose prophylaxis could be a better option in developing countries with limited economic resources.
Thesis (M.Med. (Paediatrics and Child Health)) -- University of Limpopo, 2023
Keywords: Paediatric ptients; Sever haemophilia A; Episodic treatment; Prophylactic treatment; Haemophilia; Hemophilia; Blood coagulation disorders in children; Hemophilia in children